Understanding the Body of Christ: A Literature Review on Roman Catholic Church in International Relations - Kristiono, Michael Joseph (UI Scholars Hub, 2017)
The paper is a review article on how recent International Relations (“IR”) literature perceives the Roman Catholic Church. It attempts to show how the actorness of the Church is being represented on IR literatures written especially at post-Cold War era. The time frame is chosen because attention towards transnationalism and its corresponding actors has only emerged from that period of time, thus enabling scholarly discussion on religious actors. Firstly, this article is going to trace early mention of the Catholicism and IR. Then, it is going to explain how current IR scholars analyse the Church. It is found that majority of current discussions are based upon the underlying assumption that Vatican City State, the Holy See, church network and Catholic NGOs exist as different entities. Next, the article is going to highlight recent developments which attempted to suggest the Church as – perhaps – a multi-layer being, contrary to what is currently believed. Using the logic borrowed from Catholic theology, I am offering a synthesis of the Church as a multifaceted actor, not unlike the unitary state as understood by classical realism. Therefore, this review article can also be seen as a challenge towards the collective understanding, or lack thereof, about one of the oldest surviving global political actors, the Roman Catholic Church.